Pairwise Error Probability of Distributed Space–Time Coding Employing Alamouti Scheme in Wireless Relays Networks - Duong, Trung Q.; Nguyen, Ngoc-Tien; Hoang, Trang; Nguyen, Viet-Kinh (Wireless personal communications, 2009)
In this paper, we analyze the pairwise error probability (PEP) of distributed space–time codes, in which the source and the relay generate Alamouti space–time code in a distributed fashion. We restrict our attention to the space–time code construction for Protocol III in Nabar et al. (IEEE Journal on Selected Areas Communications 22(6): 1099–1109, 2004). In particular, we derive two closed-form approximations for PEP when the relay is either close to the destination or source and an upper bound for any position of the relay. Using the alternative definition of Q -function, we can express these PEPs in terms of finite integral whose integrand is composed of trigonometric functions. We further show that with only one relay assisted source-destination link, system still achieves diversity order of two, assuming single-antenna terminals. We also perform Monte-Carlo simulations to verify the analysis.